Sponge epibionts on ecosystem-engineering ascidians: The case of Microcosmus sabatieri - Voultsiadou, E.; Kyrodimou, M.; Antoniadou, C.; Vafidis, D. (Estuarine, Coastal and Shelf Science, 2010)
The study of epibionts on habitat engineering ascidians is of increasing interest because changes in the population structure of the latter may affect associated communities, especially in the case of commercially exploited species. The solitary ascidian Microcosmus sabatieri lives on rocky cliffs in the Eastern Mediterranean and is harvested in certain Aegean areas. Its hard, wrinkled tunic is usually fouled by various epibionts both sessile and motile. Sponges are an important component of this complex and their biomass may be higher than that of the ascidian itself, strongly affecting diversity and abundance of the motile epifauna. The aim of this study was to examine in detail the structure of the epibiotic sponge assemblage on ascidians collected from their main fishing grounds in the South Aegean Sea. A rich (41 species) and taxonomically diverse sponge assemblage was found, while only eight species contributed 80% of the total sponge cover. Most of the epibiotic sponges commonly grow on the surrounding sublittoral cliffs. The encrusting sponge growth form prevailed in cover of the ascidian tunic, while two massive species dominated in terms of frequency of appearance and abundance. Ascidian dimensions, weight and volume were significantly correlated with sponge diversity, abundance and cover area, thus structuring the epibiotic sponge assemblage. Spatial patterns in sponge cover were not clear, but a general declining NW to SE trend in sponge richness, abundance and cover appeared in accordance with previous records. Sponge distribution on the ascidian tunic presented a clear pattern related with characteristic features of the ascidian: the posterior zone supported the richest and most expansive sponge fauna. The ecosystem-engineering process performed by the ascidian is enhanced by the diverse epibiotic sponge assemblage, thus further increasing habitat complexity in this space-limited, temperate, sublittoral, rocky environment.